2021
DOI: 10.21037/apm-21-127
|View full text |Cite
|
Sign up to set email alerts
|

Associations of serum cryptococcal antigen with different of clinical characteristics: a comprehensive analysis of 378 pulmonary cryptococcosis patients

Abstract: Background: Pulmonary cryptococcosis (PC) is an infection typically diagnosed in immunocompromised or immunocompetent patients, which can lead to severe disease if not treated appropriately. We aimed to determine the association between clinical manifestations, computed tomography (CT) findings, and host immune status with the serum cryptococcal antigen (CRAG) test results of PC patients. Methods:The clinical data of 378 PC patients over a 12-year period were retrospectively reviewed at Shanghai Pulmonary Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The category of proven IFD can apply to any patient, regardless of whether the patient is immunocompromised [20]. In clinical practice, CrAg has significant value as a specific biomarker in the diagnosis of cryptococcosis and evaluation of therapeutic efficacy [21]. One study showed that the sensitivity, specificity, positive predictive value, and negative predictive value of CrAg in lung tissue and serum samples were 100%, 97%, 89%, 100%, and 37.5%, 100%, 100%, and 76%, respectively [22].…”
Section: Discussionmentioning
confidence: 99%
“…The category of proven IFD can apply to any patient, regardless of whether the patient is immunocompromised [20]. In clinical practice, CrAg has significant value as a specific biomarker in the diagnosis of cryptococcosis and evaluation of therapeutic efficacy [21]. One study showed that the sensitivity, specificity, positive predictive value, and negative predictive value of CrAg in lung tissue and serum samples were 100%, 97%, 89%, 100%, and 37.5%, 100%, 100%, and 76%, respectively [22].…”
Section: Discussionmentioning
confidence: 99%
“…This case demonstrates the importance of maintaining a high index of suspicion for Cryptococcus as part of the differential in immunocompetent patients with exposure to globally endemic locations because these findings can mimic malignancy. 16 The recommendation to treat as a central nervous system disease include cryptococcocemia, evidence of dissemination, or evidence of high fungal burden based on cryptococcal antigen titer . 512.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of PC has recently increased rapidly in hosts with normal immune function (5,6). Different immune statuses may affect the pulmonary CT manifestations of cryptococcosis (7,8). The diagnosis of PC is challenging due to its diverse and nonspecific CT findings, which may mimic those of lung cancer, bacterial pneumonia or tuberculosis (5).…”
Section: Pulmonary Cryptococcosis (Pc) Is a Common Opportunistic Fung...mentioning
confidence: 99%